A Systematic Comparison of Students Attitudes Toward Practical Work in Chemistry Department Faculty of Education, Zawia -University of Zawia: A Systematic Comparison of Students Attitudes Toward Practical Work - Baroud, Najah (Universitas Islam Indonesia, 2024)
This comparative study aims to compare the attitude toward lab work. It includes two student groups in Chemistry Department, Faculty of Education - Zawia, University of Zawia- Libya. The study includes first four semesters (FFS) students, and last four semesters (LFS) students. Their attitudes were assessed via a Google Forms online questionnaires, where sent to each group separately. The number of responses sent to the researcher was 61 for FFS and 52 for LFS. The study was carried out in the fall and spring semesters of the academic year 2023-2024. A qualitative research approach was adopted. There was a substantial difference in the percentage of questionnaire responses between the FFS group and the LFS group. This outcome supports the positive attitude toward working in chemical laboratories and highlights the benefits, which include helping students develop as professionals and gain confidence. These changes take place over the lab courses, reaching their highest point during the graduation semester when a qualified teacher produced, who after that imparts information to their students